Designing Control System of Palletizing Robot Based on RobotStudio. Issue 1 (1st December 2022) - Chen, Xiaokang; Zhou, Yin; Yang, Bin; Miao, Xinghua; Li, Yanlin; Zhang, Miaorong
Abstract: According to the operational task of the palletizing robot in the intelligent manufacturing system, the layout and control process of the palletizing system are first designed. And then, the Smart Component of RobotStudio is used to design the system signal with I/O control logic, conveyor control logic, and a suction cup tool. Finally, the rationality, efficiency, and convenience of the function of the palletizing robot control system are verified by building a palletizing simulation system.